COCRYSTAL FORMULATION OF NICOTINAMIDE AND NAPROXEN AND ITS IMPACT ON SOLUBILITY, DISSOLUTION, AND MECHANICAL PROPERTIES - Mahardika Sherlin, Adinda
Naproxen (NPX) is an anti-inflammatory drug belonging to BCS class II with oral bioavalability that is dependent on its solubility. NPX shows poor solubility, dissolution, and compressibilty profile. The purpose of this study is to assess how nicotinamide (NCT) and NPX cocrystal formation affects NPX's solubility, dissolution, and mechanical characteristics. NPX-NCT cocrystals were prepared using the liquid assisted grinding method and characterized using PXRD, FTIR, SEM, and DSC. The solubility test findings of NPX-NCT cocrystal showed an increase of 1,28 times against pure NPX, while the dissolution rate testing did not show a significant increase. Evaluating the tensile strength of NPX at different compression pressures produced rather low results (< 1,7 MPa), while pressures beyond 110 MPa seemed to cause capping. In the meantime, the NPX-NCT cocrystal's tensile strength rises with increasing compression pressure, peaking at 221 MPa with a value of 2,49 MPa (2,46 times greater than NPX). Furthermore, elastic recovery analysis at various compression pressures shows that NPX-NCT cocrystals are more plastic than pure NPX.